Factors influencing small holder farmers adoption of climate SMART agriculture practices in Welmera Woreda, Central Ethiopia - Gudina, Mesay Hailu; Alemu, Esubalew Abate (Frontiers in Climate, 2024)
Adoption of climate-smart agriculture practices are believed to have significantly lessened the devastating impact of climate change on agriculture. However, in countries like Ethiopia, the adoption and use level of climate-smart agriculture practices remains low. The understanding of farmers’ levels of CSA practice adoption and influencing factors is therefore crucial. The goal of the study is to evaluate the degree to which various CSA practices were being used in the study area, as well as adoption determinants. The study was conducted in Welmera district, Oromia, Ethiopia. Three kebeles were chosen from the district, and a random sample of 306 farmers was picked. We used a cross-sectional household survey, a focus group discussion, and interviews with key informants. A multivariate probit model was employed to investigate the factors influencing the adoption of multiple climate-smart agriculture practices. According to the result, conservation agriculture, integrated soil fertility management, and crop diversification are the most often used CSA practices. The results also revealed that male farmers outperformed female farmers in terms of crop diversity and improved animal feed and feeding practice adoption. The age of farmers has a considerable and unfavorable impact on their likelihood of adopting improved soil fertility management and crop diversification practices. However, it has a positive and considerable impact on the adoption of agroforestry practices. With regards to economic factors, having a relatively big farmland area considerably enhances the adoption of conservation agriculture, enhances soil fertility management and crop diversity, and improves livestock feed and feeding methods and post-harvest technology practice. Improved livestock feed and feeding are more likely to be used with higher farm income. Having a significant number of animals strongly promotes the adoption of conservation agriculture, and access to financial services positively impacts agroforestry, diversification of crops, and postharvest technology practice adoption. Furthermore, institutional factors including access to agricultural extension services and training were discovered to be important and beneficial for crop diversification; similarly, access to field day participation was discovered to have a significant and positive impact on the adoption of conservation agriculture and improved soil fertility management practices. It is critical to raise awareness about climate change among farmers and experts, as well as to incorporate location-specific CSA practices into agricultural programs.